2017
DOI: 10.1007/s11042-017-4571-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving static audio keystroke analysis by score fusion of acoustic and timing data

Abstract: In this paper we investigate the capacity of sound & timing information during typing of a password for the user identification and authentication task. The novelty of this paper lies in the comparison of performance between improved timing-based and audio-based keystroke dynamics analysis and the fusion for the keystroke authentication. We collected data of 50 people typing the same given password 100 times, divided into 4 sessions of 25 typings and tested how well the system could recognize the correct typis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This indicates that a change in hardware would result in an increased variation in the samples. In another longitudinal study combining key timings and acoustic timings, the second session was identified as best [33]; however, their study included 50 participants typing the same phrase (‘password’) 25 times in a session, repeated 4 times. The absence of changing the typed password means direct comparisons with our work cannot be made.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that a change in hardware would result in an increased variation in the samples. In another longitudinal study combining key timings and acoustic timings, the second session was identified as best [33]; however, their study included 50 participants typing the same phrase (‘password’) 25 times in a session, repeated 4 times. The absence of changing the typed password means direct comparisons with our work cannot be made.…”
Section: Resultsmentioning
confidence: 99%
“…Other applications, already under development, are training of civil engineering personnel, safety training and visualization of data from physical experiments in virtual environments. Such applications can also be extended by undergoing developments regarding authentication utilizing keyboard dynamics [41], additional EMG sensing and face recognition, together with emotion recognition [42] and EEG sensing. The experimental setup, introduced in this article, will be reused for other evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented in this paper using a fusion system for automatic facial emotion recognition are promising. In the future, the audio features and speaker emotion detection models [43] will also be tested and fused [44] with the frame-level results.…”
Section: Conclusion and Discussionmentioning
confidence: 99%